2010
DOI: 10.1148/radiol.09090660
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction: Serial Cardiac MR Imaging Shows a Decrease in Delayed Enhancement of the Myocardium during the 1st Week after Reperfusion

Abstract: In patients with AMI and successful coronary reperfusion, the size of delayed gadolinium enhancement at CE cardiac MR imaging significantly diminished during the 1st week after infarction. Thus, timing of CE cardiac MR imaging is crucial for accurate measurement of myocardial infarct size early after AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 36 publications
6
68
0
Order By: Relevance
“…Use of thinner slices, fat-saturation prepulses, and optimized inversion times may help to improve RV LGE detection. Although some reports suggest that infarct-related edema within the viable portion of the jeopardized LV myocardium can contribute to early postinfarction LGE, 26,27 further research is warranted to assess whether peri-infarct edema plays a role in the reduction of frequency and extent of RV LGE at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Use of thinner slices, fat-saturation prepulses, and optimized inversion times may help to improve RV LGE detection. Although some reports suggest that infarct-related edema within the viable portion of the jeopardized LV myocardium can contribute to early postinfarction LGE, 26,27 further research is warranted to assess whether peri-infarct edema plays a role in the reduction of frequency and extent of RV LGE at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] The accuracy of segmental LGE expressed as segmental area of late gadolinium-enhancement (SEE) defined as enhanced percentage of segmental area, [10][11][12]16 rather than maximum transmurality in predicting segmental recovery in acute STEMI has shown promise.…”
Section: Khan Et Al Cmr Predictors Of Segmental Recovery In Stemimentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Moreover, several reports have shown that LGE, measured within days of STEMI, overestimates acute infarct size (IS) and underestimates the potential for functional recovery. [13][14][15] The accuracy of segmental LGE expressed as segmental area of late gadolinium-enhancement (SEE) defined as enhanced percentage of segmental area, [10][11][12]16 rather than maximum transmurality in predicting segmental recovery in acute STEMI has shown promise.…”
Section: Khan Et Al Cmr Predictors Of Segmental Recovery In Stemimentioning
confidence: 99%
See 1 more Smart Citation
“…35 With the combination of the inversion recovery technique described by Simonetti et al, 36 it became possible to maximize the contrast between viable and 37,38 There is significant decrease in the total extent of LGE between day 1 and day 7 post-MI. [39][40][41] CMR can be used in assessing MI size up to 1 week after the acute ischemic event. With time, the size of the infarct decreases as a result of resolution of tissue edema and gradual contraction of the resultant scar tissue by as much as 25% over a period of 4-8 weeks.…”
Section: Late Gadolinium Enhancementmentioning
confidence: 99%